2011
DOI: 10.3324/haematol.2011.048694
|View full text |Cite
|
Sign up to set email alerts
|

A role for activated endothelial cells in red blood cell clearance: implications for vasopathology

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPhosphatidylserine exposure by red blood cells is acknowledged as a signal that initiates phagocytic removal of the cells from the circulation. Several disorders and conditions are known to induce phosphatidylserine exposure. Removal of phosphatidylserine-exposing red blood cells generally occurs by macrophages in the spleen and liver. Previously, however, we have shown that endothelial cells are also capable of erythrophagocytosis. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 44 publications
6
58
0
1
Order By: Relevance
“…The bound RRx-001-modified RBCs, abundant in oxidized lipids, iron, and heme, are phagocytized by TAM [19,20], leading to their repolarization from M2-like to M1-like. As a result, the RRx-001-bound red blood cell resembles the 'Trojan Horse' of Greek mythology, bearing abundant free radicals in the form of iron, heme, and oxidized lipids, which leads to repolarization of the TAMs in the hypoxic tumor environment ( Figure 5(c)).…”
Section: Tumor Microvascular Occlusion and Trojan Horselike Rbc Phagomentioning
confidence: 99%
“…The bound RRx-001-modified RBCs, abundant in oxidized lipids, iron, and heme, are phagocytized by TAM [19,20], leading to their repolarization from M2-like to M1-like. As a result, the RRx-001-bound red blood cell resembles the 'Trojan Horse' of Greek mythology, bearing abundant free radicals in the form of iron, heme, and oxidized lipids, which leads to repolarization of the TAMs in the hypoxic tumor environment ( Figure 5(c)).…”
Section: Tumor Microvascular Occlusion and Trojan Horselike Rbc Phagomentioning
confidence: 99%
“…apoptosis bodies[35], senescent neutrophils[36] and red blood cells[37]. The phagocytosis of necrotic cells induces activation of ECs by releasing TGF-β1 and IL-6 [38, 39] and increases ICAM-1 expression to facilitate macrophage adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…[40] In this scenario, phagocytosis dysreguates EC function and eventually leads to cell death. [37] ECs have also been shown to phagocytize polymer particles. [41-43] In contrast to enhanced macrophage phagocytosis, the phagocytic activity of ECs decreased upon microparticle treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,20 Endothelial cells possess a strong ability to engulf a variety of cell types. [21][22][23] Thus, it is reasonable that endothelial cells are considered ''non-professional phagocytes.'' 23 Similar to these reports, we found that endothelial cells derived from humans can engulf human platelets.…”
Section: Discussionmentioning
confidence: 99%